An Installation Plan For The Papi Led Constant Current Regulator At Adi Soemarmo International Airport - Syairi Anwar; Muhammad Caesar Akbar; Mohammad Alviannanta Masror (Jurnal Scientia, 2024)
At every airport, there is a facility known as a taxiway, which is a special path that connects the runway with the aircraft parking area (apron) around the terminal, and vice versa. This taxiway consists of several types, such as exit taxiway, parallel taxiway, and high-speed taxiway. The main function of a taxiway is as a connecting facility, so in planning it must pay attention to various provisions such as the distance between the taxiway and the runway, taxiway width, wheel clearance, slope, visibility distance, and also the taxiway strip. This research uses qualitative methods to produce findings. By adding a circuit to the taxiway, the load on the constant current regulator (CCR) in circuit C becomes lighter, and the cable route from the CCR on the south side becomes more efficient and easier to handle troubleshooting problems. In the process of adding circuits to taxiway lights, preparations that need to be considered include submitting an application for making an airport pass, preparing a detailed work plan by the worker, as well as submitting material approval. Work implementation must comply with regulations and Standard Operating Procedures (SOP).